An integrated approach for prioritizing the barriers to airport service quality in an intuitionistic-fuzzy environment - S. Habibollah Mirghafoori; Mohammad Reza Izadi; Ali Daei (Cogent Business & Management, 2018)
Airports today, despite the complexity of their service environment and multicultural nature, are expected to provide high-quality services to satisfy their passengers. This way they will be able to gain competitive advantages. Hence, improving the quality of airport services has become increasingly significant. In this paper, the main components of the airport services quality with the greatest impact on the customer satisfaction have been derived based on previous articles as well as interviews with experts in this field and travelers. Subsequently, the comments of passengers were received by distributing questionnaires. Eventually, using failure mode and effects analysis (FMEA) approach along with entropy and VIKOR techniques, the risk factors were evaluated and ranked in an intuitionistic triangular fuzzy environment. The findings of this research can be addressed to the airport management team to review and reform their services and facilities. Yazd international airport was considered as a case study of this paper.
Keywords: 650